2021
DOI: 10.29407/js_unpgri.v7i1.15642
|View full text |Cite
|
Sign up to set email alerts
|

Level of physical activity of Indonesian esport athletes in the piala Presiden esport 2019

Abstract: Background: In the past years, Esport has been a phenomenon. It lies in a discussion of whether accepting esport as a part of sport categories or not. In fact, many argue about this because it has an impact on the physical activity and lifestyle of the players. This study focuses on the analysis of physical activity and lifestyle of esport athletes competing in annual sporting events throughout Indonesia. Method:  In this study data collected from 50 athletes consisting of all men. The measurement method used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
6
0
4
Order By: Relevance
“…The 1-minute bout accelerometer-assessed physical activity data is substantially higher than previous esports surveys reporting self-reported sedentary time [ 9 , 10 , 17 , 24 ], with weekly MET-min − 1 being lower than what has been reported through previous IPAQ’s in esports populations [ 10 , 12 , 73 ]. These findings raise concerns that previous international esports surveys using any version of the IPAQ may be under reporting the level of physical inactivity within esports [ 10 , 12 , 24 , 73 ]. Concerns of under reporting of physical inactivity through the IPAQ-LF have been raised within global surveillance studies [ 64 ].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The 1-minute bout accelerometer-assessed physical activity data is substantially higher than previous esports surveys reporting self-reported sedentary time [ 9 , 10 , 17 , 24 ], with weekly MET-min − 1 being lower than what has been reported through previous IPAQ’s in esports populations [ 10 , 12 , 73 ]. These findings raise concerns that previous international esports surveys using any version of the IPAQ may be under reporting the level of physical inactivity within esports [ 10 , 12 , 24 , 73 ]. Concerns of under reporting of physical inactivity through the IPAQ-LF have been raised within global surveillance studies [ 64 ].…”
Section: Discussionmentioning
confidence: 73%
“…Our findings suggest that the IPAQ significantly over-reports physical activity time in e’athletes. Previous health survey’s using the IPAQ within esports have shown similar physical activity levels suggesting that the majority of e’athletes are exceeding the international PA guidelines [ 10 , 12 , 24 , 73 ]. When using a different questionnaire, 66.9% of a German esports’ population reported they perform more than 2.5 h a week of MVPA, although the validity of this questionnaire is also unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This research project was completed in December of 2021. A long-form International Physical Activity Questionnaire (IPAQ) was used to assess physical activity, which was completed independently (self-administration) both online (Google form) and offline (questionnaire paper) [16]. The questionnaire contains 27 questions divided into several domains of physical activity, such as weekday physical activity, travel-related physical activity, neighborhood activities, and recreational physical activities.…”
Section: Martials and Methodsmentioning
confidence: 99%
“…The virtual football players in the Portuguese Football Federation (FPF) appeared to be very active (Pereira et al, , 2021, as did the MOBA players in Indonesia (Paramitha et al, 2021).…”
Section: Physical Activity Levelmentioning
confidence: 99%
“…Trotter et al (2020) showed that the top 10% of athletes were significantly more active than the other 90% (p < 0.05), and that the players' in-game rank was positively associated with the number of days they were physically active per week (p < 0.01). The studies by Kari and Karhulahti (2016), Kari et al (2019), Giakoni-Ramírez et al (2022), and Paramitha et al (2021 targeting high-level and/or professional players reported that these players were very active. On the other hand, players who represented their countries in international competitions (3) and collegiate athletes (4-5), who are assumed to have a high level of expertise, did not appear to be very active, bringing into question the idea that high-level esports players are more active.…”
Section: Physical Activity Levelmentioning
confidence: 99%